Risk Management and Performance of Manufacturing Industries in Nigeria - Adeoye, Emmanuel; Akinsunmi, Dayo (CV ODIS, 2023)
Risk management practices have played a crucial role in the performance and sustainability of manufacturing companies. In an increasingly complex and volatile business environment, effective risk management became essential for mitigating uncertainties, protecting assets, and optimizing operational efficiency. Therefore, this study aimed to examine the relationship between risk management practices and the performance of manufacturing companies in Nigeria. Using a quantitative research design, the study employed a cross-sectional survey and analyzed secondary data from audited financial statements of prominent manufacturing entities over a 10-year period (2011-2021). The study focused on two key variables: risk management (measured by working capital and investment capital) and performance (measured by return on assets and return on capital employed). The findings revealed a strong positive relationship between the proxies of risk management, highlighting the importance of effectively managing working capital and investment capital. The regression analysis demonstrated that working capital and investment capital significantly influenced the performance of manufacturing companies, as measured by return on assets and return on capital employed. The results supported the rejection of the null hypothesis, indicating that risk management practices had a significant impact on firm performance in the Nigerian manufacturing sector. It is recommended that manufacturing companies in Nigeria prioritize and strengthen their risk management strategies. This involves optimizing working capital and investment capital to enhance overall performance. The findings provide valuable insights for policymakers, practitioners, and stakeholders in the manufacturing industry, underscoring the need to integrate robust risk management strategies to achieve sustainable growth and competitiveness.